BLACK WOOL AND VINTAGE SHOES: THE WELLINGTON LOOK (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
“He told me I didn’t look like I was from Wellington,” a friend, from a small town almost two hours away, confided to me over a cocktail in a downtown bar. This article asks, what is the Wellington look that this statement describes? How does it produce and reflect Wellington’s reputation as the locus of arts and politics in Aotearoa/New Zealand? It examines how the inhabitants of Wellington weave the fabric of the city together through their dress, analyzing how Wellington-based media, boutiques, designers, and locals together create a style that is distinctively ‘Wellington.’